The long tail : why the future of business is selling less of more. - Anderson, Chris, 1961- (New York : Hyperion, 2006)
What happens when the bottlenecks that stand between supply and demand in our culture go away and everything becomes available to everyone? "The Long Tail" is a powerful new force in our economy: the rise of the niche. As the cost of reaching consumers drops dramatically, our markets are shifting from a one-size-fits-all model of mass appeal to one of unlimited variety for unique tastes. From supermarket shelves to advertising agencies, the ability to offer vast choice is changing everything, and causing us to rethink where our markets lie and how to get to them. Unlimited selection is revealing truths about what consumers want and how they want to get it, from DVDs at Netflix to songs on iTunes to advertising on Google. However, this is not just a virtue of online marketplaces; it is an example of an entirely new economic model for business, one that is just beginning to show its power. After a century of obsessing over the few products at the head of the demand curve, the new economics of distribution allow us to turn our focus to the many more products in the tail, which collectively can create a new market as big as the one we already know.
Keywords: Economie; Marketing